Antidepressant use in the Canary Islands (Spain): a retrospective study of provincial, island and municipal trends and associated factors - Alexis Oliva; Vanessa Moreno; Mariana Sapino; Sandra Dévora; Susana Abdala-Kuri (Frontiers in Pharmacology)
IntroductionThe presence of a diagnosis by a general practitioner is a major reason for the use of antidepressant (ADs). However, the simultaneous analysis of several and interrelated socioeconomic and demographic factors could provide a picture of the distribution of AD use in a given population across diverse geographical regions and socioeconomic backgrounds. The aim of the present study was to provide a picture of the trends in the consumption of ADs at the provincial, island and municipal levels for the period 2016–2021 in the Canary Islands (Spain), as an example of a geographically isolated area. To this end, several factors were analyzed, such as living in a rural or urban area, the population over 65 years of age, the population density or the socioeconomic status.MethodsData were extracted from the community pharmacy wholesaler at the population level. A model with two nested fixed factors and a co-variable were used to analyze the trends in the use of ADs and the factors associated. Dispensation ADs use was measured as defined daily doses (DDD) per 1000 inhabitant per day. This provided total overall dispensation of AD and its rate of change for each island, as well as differences in dispensation at the island and municipal level.ResultsOver the study period, prescription rates increased steadily at all population levels, although the level of dispensing and the rate of variation varied between island and municipalities but no between provinces. The data on the use of ADs at the level of the province and islands are more accurate because they include the entire population that is resident in that zone. At the municipal level, there is a bias, but it is difficult to quantify. The prescription patterns at municipal level were similar to those observed at island level, although with small variations in the dispensation level. Selective serotonin reuptake inhibitors (SSRIs) were the most commonly used, followed by “other ADs,” whereas the use of tricyclic ADs remained stable. 1n addition, all AD drugs are equally available regardless of the geographical area of residence or socio-economic status although the type of AD and ranking varied slightly between islands due to the differences in general medical practice.ConclusionThe observed differences in ADs use between rural and urban areas cannot be attributed to the factors of urbanization, population age, population density and socioeconomic status. However, the medical practices, the social and cultural traditions of each island, may provide insights into the underlying reasons for this variation.